Socioeconomic Dimensions in Locations by Clusters Identified for the Population Establishing Residence (including External Migration) in Another Locality at LAU 2/NUTS 5 in Romania - Lincaru, Cristina; Pîrciog, Speranța; Atanasiu, Draga; Drăgoiu, Codruța (Calitatea Vieții, 2015)
Identifying locations that are part of the LAU2 two types of clusters HH and LL indicates similarities at the level of the population establishing residence (including external migration) in another locality, using spatial statistical analysis method Local Indicators of Spatial Association LISA (Anselin 1995, 1996) and calculated in GeoDA Software. Each location LAU2’s type (national, HH or LL) is profiled as calculated in SPSS by the statistical mean of characteristics relevant indicators to the labour market: the number of registered unemployed (2010 and 2013), number of employees (2010), average population density / km2 (1992 – census data) and average number of people entering the LAU2 following the change of residence by reference environment (urban/rural) and national levels in 1990 and 2009 in Romania. Data source is provided by National Institute of Statistic INS – TEMPO online database, socioeconomic indicators detailed level LAU 2 / NUTS 5. These research results have been achieved in the Project NUCLEU PN – 420 118: spatial distribution of cohesion policy indicators, made in 2014, and results are used in Dynahu Project.